MARICULTURE IMPACTS ON THE BENTHONIC ICTHYOFAUNA OF ITAGUÁ BAY, UBATUBA, SOUTHEAST BRAZIL - Vanessa Villanova Kuhnen; Leticia de Góis Costa; Kleper de Lima Raiol; Otávio Mesquita de Sousa; Eduardo Gomes Sanches (Boletim do Instituto de Pesca)
Due to the decline of fishing stocks, aquaculture has been expanding throughout the world. Taking into account the possibility of conflicts of aquacultural activities in areas of environmental protection, this study aims at assessing the effects of mariculture upon the local ichthyofauna of Itaguá Bay in Ubatuba, São Paulo state, Brazil, which is within a marine protection area. In order to do so, the fish community was analyzed in areas with mussels and macroalgae farms and in areas without any maricultural activities. After six months of sampling efforts, 230 individuals were captured from 19 different species and 15 families. There was no difference in catchability, richness, diversity, and evenness among the areas. Nevertheless, the species composition was distinct in areas where mussels were farmed. These areas have presented twice as much fish biomass than the others. Based on these results, we can observe that the environmental alterations caused by mussel farming, are sources of habitat complexity, hence able to enrich the marine fauna of the region. Thus, we conclude that mariculture, specifically mussel farming, has a positive impact on ichthyofauna, contributing to biodiversity maintenance in protected areas.